Writing Biographical Fiction: Some Personal Reflections. (2nd January 2016) - Parini, Jay
Abstract : Jay Parini, author of three biographies and three biographical novels, reflects on the different strategies and approaches to both genres, clarifies the different kinds of "truths" each pictures, discusses the kind of ethical responsibilities authors have to their subject, and considers shifts in the understanding of history in relation to the rise of biofiction.